2017
DOI: 10.1186/s40635-017-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood microRNA markers are associated with acute respiratory distress syndrome

Abstract: BackgroundMicroRNAs (miRNAs) can play important roles in inflammation and infection, which are common manifestations of acute respiratory distress syndrome (ARDS). We assessed if whole blood miRNAs were potential diagnostic biomarkers for human ARDS.MethodsThis nested case-control study (N = 530) examined a cohort of ARDS patients and critically ill at-risk controls. Whole blood miRNA profiles and logistic regression analyses identified miRNAs correlated with ARDS. Stratification analysis also assessed selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…MiR-424 was shown to be a protective biomarker. Zhu concluded stating in addition to the miRNA, addition of the LIPS can improve the risk estimate of ARDS [69].…”
Section: Biomarkersmentioning
confidence: 99%
“…MiR-424 was shown to be a protective biomarker. Zhu concluded stating in addition to the miRNA, addition of the LIPS can improve the risk estimate of ARDS [69].…”
Section: Biomarkersmentioning
confidence: 99%
“…miR-181 has been designated as a significant inflammatory response marker in whole blood analysis associated with sepsis-induced acute respiratory distress syndrome [ 72 ]. Decreased miR-181a expression reduced cell apoptosis of LPS-treated lung epithelial cells by targeting Bcl-2 [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same group also reported analyses that compared microRNA expression in whole blood samples from patients with ARDS and critically ill at-risk control patients (Zhu et al 2017). They revealed that the levels of miR-181a or miR-92a were positively correlated with a risk for the development of ARDS, whereas miR-424 was negatively correlated with a risk for ARDS.…”
Section: The Changes and The Roles Of Micrornas In Ardsmentioning
confidence: 99%